2014
DOI: 10.1108/s1474-787120140000024006
|View full text |Cite
|
Sign up to set email alerts
|

The Profitability and Performance Measurement of U.S. Regional Banks Using the Predictive Focus of the “Fundamental Analysis Research”

Abstract: Purpose À This paper examines the profitability and performance measurement of U.S. regional banks during the period 1994À2011, using the GMM estimator technique. Our study extends prior research by including several factors not previously considered using U.S. data.Approach À We use bank-specific, industry-specific, and macroeconomic determinants of profitability contemporaneous with our performance indicators. We follow the accounting fundamental analysis path in explaining the bank performance.Findings À Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 76 publications
(259 reference statements)
3
51
1
Order By: Relevance
“…Higher the ratio, more stable and efficient the bank is. While the relationship of this variable to profitability may vary across the stages of the business cycle (Berger, 1995) we expect it will have an overall positive relationship to profitability (Growe et al, 2014).…”
Section: Capital Adequacymentioning
confidence: 99%
“…Higher the ratio, more stable and efficient the bank is. While the relationship of this variable to profitability may vary across the stages of the business cycle (Berger, 1995) we expect it will have an overall positive relationship to profitability (Growe et al, 2014).…”
Section: Capital Adequacymentioning
confidence: 99%
“…Return on assets (ROA), Return on equity (ROE), and Net interest margin (NIM) are the three measures of profitability supported by the literature review (see Growe et al 2014, Alberttazzi and Gambacorta, 2009, Angbazo, 1997, Demirguc-kunt and Huizinga, 2008, Golin and Delhaise (2013. Return on assets (ROA) is used as a primary measure of bank profitability.…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The negative effect is expected here. ( Growe. et al, 2014, Ben Naceur & Goaied, 2008Kosmidou et al, 2005) Macroeconomic factor Per capita Real Gross Domestic Product Growth (PRGDPG).…”
Section: Negative On Profitabilitymentioning
confidence: 99%
“…Forster and Shaffer (2005) argue that banks' efficiency may generally be considered as a function of both bank-specific characteristics and financial market factors. Furthermore, Growe et al (2014) investigated the profitability and performance measurements of U.S. regional banks through the period 1994-2011, by applying the efficiency ratio, i.e., (non-interest income over total income). They indicated that the efficiency ratio is a measure of banks' efficiency, and found that there is a significant and negative relationship between profitability and the efficiency ratio.…”
Section: Bank-specific Factors and Bank Efficiencymentioning
confidence: 99%
“…Bank efficiency ratio is measured by the cost-income ratio (Goddard et al, 2010). Hence, the measurement of the cost-income ratio is noninterest expenses over total revenue (NIE/TR), where total revenues are equals to (Non-Interest Income + Net Interest Income) (Forster and Shaffer, 2005;Growe et al, 2014) (Table 2). World Bank data; the plan of accounts that all FCC financial institutions have to report to their Central Banks on a yearly basis.…”
Section: Fig 1: Proposed Conceptual Frameworkmentioning
confidence: 99%